2019
DOI: 10.1371/journal.pone.0210626
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dose distributions in gross tumor volume between boron neutron capture therapy alone and combined boron neutron capture therapy plus intensity modulation radiation therapy for head and neck cancer

Abstract: Nine patients with recurrent head and neck (H&N) cancer received boron neutron capture therapy (BNCT) in one fraction at the Tsing-Hua Open pool reactor (THOR) utilizing the THORplan treatment planning system (TPS). The aims of the present study were to evaluate the use of intensity modulated radiation therapy (IMRT) of 45 Gy in 20 fractions to compensate for the dose heterogeneity in gross tumor volume observed with single-fraction BNCT with mean prescription dose 19 Gy (w), and to evaluate planning quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Using nine patients with recurrent head and neck cancer from THOR, Lee et al analyzed the dose distributions between BNCT alone and BNCT with IMRT. BNCT with IMRT had GTV conformity and improved homogeneity compared to BNCT monotherapy (60).…”
Section: Recurrent Head and Neck Cancersmentioning
confidence: 97%
“…Using nine patients with recurrent head and neck cancer from THOR, Lee et al analyzed the dose distributions between BNCT alone and BNCT with IMRT. BNCT with IMRT had GTV conformity and improved homogeneity compared to BNCT monotherapy (60).…”
Section: Recurrent Head and Neck Cancersmentioning
confidence: 97%
“…Recently, Jai-Cheng reported the comparison of dose distributions in gross tumor volume between BNCT alone and BNCT combined with intensity modulation radiation therapy (IMRT) for head and neck cancer. He suggested that compared to single-fraction BNCT, the multi-fraction IMRT combined with single-fraction BNCT improves the treatment conformity and homogeneity and possibly local tumor control, especially for tumor whose volume is greater than 100 cm [127]. A recent study, published in Radiotherapy and Oncology, demonstrated the efficiency of BNCT in the treatment of locally recurrent head and neck squamous cell carcinoma (HNSCC) patients and also the factors that are favorable for the treatment response and survival [128].…”
Section: Recurrent Head and Neck Regional Tumor Treatment With Bnctmentioning
confidence: 99%
“…A second clinical trial, also phase I/II, was started in 2014 combining BNCT with IGRT and IMRT to try to reduce re-recurrences [ 130 ]. As of 2019, Lee et al, provided evidence suggesting that the single-session dose distribution in terms of homogeneity and conformity might improve when combined with multifraction IMRT [ 131 ]. Additionally, in Taiwan, BNCT was evaluated as a salvage therapy for malignant brain tumors, with preliminary results published in 2020 showing significant effects on maintaining a good quality of life and possibly prolonging a patient’s survival [ 132 ].…”
Section: Clinical Possibilities Of Bnct and Future Perspectivesmentioning
confidence: 99%